The Oversight Function of the Nigerian National Assembly: A Legal and Research Analysis - Ecoma, Lequome E.; Ecoma, Bonnievolo E.; Ecoma, Evalsam S. (Nagari Law Review, 2024)
Around the world, legislatures are viewed as symbols of democratic authority, and are essentially defined by the extent or degree to which they efficiently and effectively perform their core functions of representation, law-making and oversight. The oversight function has been variously described as a critical component of good governance, an instrument of nation building, and the cornerstone of democracy. It is largely regarded as the central instrument through which the legislature holds the executive branch of government to account. In settings where the function is performed efficiently and effectively, it ensures greater executive compliance with the content and intent of laws, promotes transparency, good governance and accountability, and asserts the power, influence and authority of the legislature as a defender of the interests of the citizenry. Where it is poorly performed, the reverse is the case. Over the years, the Nigerian National Assembly has been largely perceived as an ineffective legislature especially as the exercise of its oversight function has been fraught with several challenges that question the integrity of the function and the institution itself. Through a review of statutory provisions and extant literature whilst relying on the doctrinal research methodology, the paper examines research-based perspectives on the performance of the oversight function by the National Assembly, with a view to unveiling current research on the exercise of the function, and ascertaining the state of the function in the governance framework of the country. The paper concludes by making recommendations for reform of the function based on findings made.